Social Capital, Trust, and Well-being in the Evaluation of Wealth - Hamilton, Kirk; Helliwell, John; Woolcock, Michael (World Bank, Washington, DC, 2016)
This paper combines theory with data from different domains to provide an empirical analysis of the scale and variability of social capital as wealth. The analysis is used to argue, given what has been learned from the literature on social capital, that the welfare returns to investing in trust could be substantial. Using data from 132 nations covered by the Gallup World Poll, the paper presents a range of estimates of the wealth-equivalent values of social trust. Such values are usually not included in national or global accounts of income and wealth. In the light of the estimated importance of social trust as a component of wealth and well-being, the paper concludes with some policy options for how social trust might be better built and sustained.